Managing congestion: economics of price and lottery rationing. - Kerr, G. N. (Journal of Environmental Management, 1995)
The writer demonstrates how efficient capacity differs between two competing resource allocation mechanisms, one of which is efficient—price—and one of which is fair—lottery. The welfare theoretic implications of adopting lottery allocation as opposed to price allocation are described from the perspectives of economic efficiency and the benefits obtained by resource users and suppliers. It is discovered that risk-neutral resource users will always favor lottery allocation over price allocation as it is never in risk-neutral resource users' interests to have price allocation imposed. Findings are analyzed using a linear constant crowding demand function, in which case it is discovered that the efficient capacity for lottery rationing exceeds the efficient capacity where price is to be used to allocate a congestible resource. It is concluded that objectives may be better met by combined use of allocation mechanisms, the implications of which are examined using the linear demand model.